PENGARUH PEMBELAJARAN ICI TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA DITINJAU DARI GAYA KOGNITIF - DEVIANA, DEVIANA; PRAMARTHA, I NYM BAGUS (E-Jurnal Matematika; Vol 9 No 1 (2020), 2020)
The purpose of this research is to find out : (1) the effect ICI model for attitude and ability of mathematical representation in terms of student's cognitive (2) how the model of learning ICI can affect the attitude and the ability of mathematical representation in terms of students' cognitive. The research type is a combination of research using concurrent embedded design with  mixed methods. Then, quantitative methods use post test design only control group design and analyzed using MANCOVA while qualitative method using descriptive research with data reduction, data presentation and verification. The results showed that: (1) learning with the ICI Model has a positive effect on Attitude and Ability of Mathematical Representation Viewed From Student Cognitive Styles on Line and Corner Material Class (? = 30.319, p> 0.05 ), (2) Students with FI cognitive style tend to have fulfilled three components of attitude and stages of mathematical representation; students with cognitive style field dependent tend not to be able to show attitude that refers to the three components of mathematical attitudes and have been able to understand the problems but in representing less and not yet able to complete the solution of the problems given.